Microstructure Analysis of Laser Welded Ferritic Stainless-Steel Interconnect for Solid Oxide Fuel Cell - Mohamad Rodzi , Anis Syazwani; Abd Rahman , Hamimah; Mohd Faizal Tukimon, (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Solid Oxide Fuel Cells (SOFC) require durable and thermally stable interconnect materials, and ferritic stainless steels like AISI 430 have emerged as a strong candidate due to their cost-effectiveness and good oxidation resistance. In this study, laser welding was used to join AISI 430 stainless steel plates, aiming to maintain structural integrity while minimizing thermal distortional important factor in fuel cell stack assembly. Microstructural analysis was carried out across the weldment, focusing on the fusion zone (FZ), heat-affected zone (HAZ), and base metal (BM). The weld metal exhibited a structure of ferrite while the HAZ showed distinct grain growth and refinement patterns depending on heat input. Fine precipitates and microstructural changes at the grain boundaries were also observed, which could influence the electrical and mechanical performance of the interconnect in long-term SOFC operation. These findings contribute to a better understanding of how laser welding affects the internal structure of ferritic stainless steels and support efforts to optimize welding techniques for high-temperature fuel cell applications.